If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4(x + 1) = 9 + -2x Reorder the terms: 3x + -4(1 + x) = 9 + -2x 3x + (1 * -4 + x * -4) = 9 + -2x 3x + (-4 + -4x) = 9 + -2x Reorder the terms: -4 + 3x + -4x = 9 + -2x Combine like terms: 3x + -4x = -1x -4 + -1x = 9 + -2x Solving -4 + -1x = 9 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -4 + -1x + 2x = 9 + -2x + 2x Combine like terms: -1x + 2x = 1x -4 + 1x = 9 + -2x + 2x Combine like terms: -2x + 2x = 0 -4 + 1x = 9 + 0 -4 + 1x = 9 Add '4' to each side of the equation. -4 + 4 + 1x = 9 + 4 Combine like terms: -4 + 4 = 0 0 + 1x = 9 + 4 1x = 9 + 4 Combine like terms: 9 + 4 = 13 1x = 13 Divide each side by '1'. x = 13 Simplifying x = 13
| 7(a+5)=4a | | 6m+2=3m+11 | | 5x=-10(2x-125) | | 1/3*14/1/3 | | -3x^2+2ax-3a=0 | | 15x+4y=302 | | 1/2-4/12 | | 0.25x+3=x | | 5x/-10=2x-125 | | 8(w-6)=2q | | 7/8=h4 | | 12-5(x+4)=15x | | 2sin^2x=6 | | x^2+5x-4=100 | | 4.75=log(0.01005-x/x) | | 5x-2/8 | | 7+x-x=2 | | (2x^2)-30x=0 | | 11.4-22.52z=84.1 | | 3p+4=4(p+3) | | 5(x+4)=15x | | (2x^2)-2x=0 | | 3(x+2)=3x+4+2 | | 2(m+3)=4 | | (3x^2)+3x=0 | | 3x+21=3x(35)+3 | | 8(10-6q)+3(-7-2)= | | ((x)/(x-2)) | | 3xty=-12 | | 9x+35=112 | | (7x^2)-42x=0 | | x+(x+4)+(3x+21)=180 |